Mycotoxin and Food Safety in Developing Countries - Anthony Makun, Hussaini (IntechOpen, 2013)
This book provides information on the incidence of fungi and mycotoxins in some African countries, the health implications and possible intervention control strategies for mycotoxins in developing countries and in Africa in particular. It will therefore be of interest to students, educators, researchers and policy makers in the fields of medicine, agriculture, food science and technology, trade and economics. Food regulatory officers also have quite a lot to learn from the book. Although a lot of the generated data in the area of mycotoxicology are available to the developed world, information on the subject area from Africa is scanty and not usually available in a comprehensive form. This book attempts to address the gap. Being an open access book, it will be of great benefit to scientists in developing countries who have limited access to information due to lack of funds to pay or subscribe for high quality journals and data from commercial publishing and database companies.